Analytical Method for Quantifying Monoterpenoids (p-Cymene and Myrcene) in Nanoemulsions Using High-Performance Liquid Chromatography - Lobato Duarte, Jonatas [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Tavares Junior, Alberto Gomes [UNESP]; Chorilli, Marlus [UNESP] (Oxford University Press (OUP), 2024)
Background: Myrcene and cymene, aromatic monoterpenes found in plants and essential oils, possess distinctive aromatic qualities. However, their volatility and limited solubility pose challenges in precise handling and formulation. Meanwhile, nanoemulsions emerge as promising drug delivery systems, improving the bioavailability and stability of these active ingredients. Objective: This article aimed to develop an HPLC method for the quantification of two monoterpenoids, p-cymene and myrcene, in nanoemulsions. Method: The method used a Phenomenex® SynergiTM Fusion-RP column (150 mm × 4.6 mm id, 4 lm particle size) on an HPLC system with isocratic elution. The mobile phase was composed of acetonitrile and water (60:40, v/v) and was validated in terms of specificity, linearity, accuracy, precision, robustness, and selectivity. Results: The method provided accurate and precise results with a correlation coefficient of 0.999 and RSD values of less than 2%. The method can be used for quality control of nanoemulsions containing these monoterpenoids and as a reference for future studies on their efficacy and stability. Conclusions: The study demonstrates the feasibility of using HPLC for the quantification of monoterpenoids in nanoemulsions and its potential as a quality control tool for nanoemulsion-based drug delivery systems. Highlights: The method’s accuracy, precision, and reliability, as evidenced by high correlation coefficients and low RSD values, underscore its suitability for ensuring the consistent formulation of these monoterpenoid-containing nanoemulsions, while also serving as a reference point for future research endeavors in this field.